Development of 'UR-System 2': a training system for recovery of motor function of plegic upper limb after stroke. (1st November 2016) - Morita, Yoshifumi; Toya, Norihiro; Takeichi, Ryosuke; Hattori, Hitomi; Tanabe, Hirofumi; Takagi, Yoshiaki; Hasegawa, Norio
Abstract: We developed a new training system, called 'UR-System 2', for the recovery of motor function of a plegic upper limb after stroke. UR-System 2, which was redesigned based on knowledge gained from clinical tests using UR-System 1, was newly equipped with a function for testing the motor function of patients, such as isolated movement. In order to verify the effectiveness of UR-System 2, we conducted the following procedures: we verified the safety of training in healthy persons; we gathered standard data on pronation and supination of healthy forearms during tests; and, we verified that the test function was effective in evaluating the recovery effect of isolated movement in two hemiplegic patients. Abstract :